Key role of reactive oxygen species-scavenging system in nitric oxide and hydrogen sulfide crosstalk-evoked thermotolerance in maize seedlings - Sun, Yu-Ying; Wang, Jia-Qi; Xiang, Ru-Hua; Li, Zhong-Guang (Frontiers in Plant Science, 2022)
Nitric oxide (NO) and hydrogen sulfide (H2S) are novel signaling molecules in plants, which participate in plant growth, development, and response to stress. Here, treatment of maize seedlings with sodium nitroprusside (SNP, NO donor) up-regulated LCD1 expression and L-cysteine desulfhydrase and D-cysteine desulfhydrase activities, which in turn increased endogenous H2S level compared with the control. SNP-triggered effects were enhanced by sodium hydrosulfide (NaHS, H2S donor), but weakened by NO scavenger 2-(4-carboxyphenyl)-4,4,5,5- tetramethylimidazoline-1-oxyl-3-oxide and H2S scavenger hypotaurine (HT) alone, while NaHS had no significant effect on nitrate reductase (NR, NO-producing enzyme) activity and gene expression. These data indicate that NO could trigger H2S signaling in maize seedlings. To further investigate effect of NO and H2S crosstalk on thermotolerance in maize seedlings, the thermotolerrance parameters and reactive oxygen species-scavenging system were estimated. The results show that SNP increased survival rate and tissue viability, decreased malondialdehyde accumulation and electrolyte leakage in maize seedlings under heat stress (HS), implying NO could improve the thermotolerance of maize seedlings. NO-improved thermotolerance was impaired by H2S inhibitor DL-propargylglycine (PAG) and scavenger HT alone. Similarly, SNP up-regulated DHAR and GR1 expression, ascorbate peroxidase, glutathione reductase, and catalase activities, as well as ascorbic acid, glutathione, flavonoids, carotenoids, and total phenols levels, reduced hydrogen peroxide and superoxide radical accumulation in maize seedlings under HS compared with the control. These physiological effects were weakened by PAG and HT alone. These data hint that NO-H2S crosstalk could evoke the thermotolerance in maize seedlings, and reactive oxygen species-scavenging system played a key role in the NO-H2S crosstalk-evoked thermotolerance.